Green Synthesis of Polypogon monspeliensis–Based Silver Nanoparticles and Their Multifunctional Biomedical Potential - Alrudainy, Alaa M.; Mshari, Ahmed (Academia Open, 2026)
General Background: Green synthesis of silver nanoparticles has gained attention as a sustainable approach to produce bioactive nanomaterials for biomedical use. Specific Background: Polypogon monspeliensis contains diverse phytochemicals that can function as reducing and stabilizing agents in plant-mediated nanoparticle synthesis. Knowledge Gap: Its potential as a green bioresource for fabricating multifunctional silver nanoparticles remains insufficiently explored. Aims: This study aimed to synthesize, characterize, and evaluate the antibacterial, antioxidant, and anticancer activities of P. monspeliensis–derived silver nanoparticles (Pol-AgNPs). Results: Pol-AgNPs were successfully synthesized, exhibiting crystalline, quasi-spherical particles (≈51–69 nm) with notable dose-dependent antibacterial activity, strong DPPH radical scavenging capacity, and selective cytotoxicity against A549 lung cancer cells. Novelty: The work demonstrates the dual functional role of P. monspeliensis extract in nanoparticle synthesis and bioactivity. Implications: Pol-AgNPs represent promising eco-friendly nanomaterials for future biomedical applications. Keywords : Green Synthesis, Polypogon Monspeliensis, Silver Nanoparticles (AgNPs), Antibacterial And Antioxidant Activity, Anticancer Nanomaterials Highlight : <article class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" tabindex="-1" data-turn-id="request-WEB:a692f13a-6008-4e31-870c-df4a8a8d9ca3-1" data-testid="conversation-turn-2" data-scroll-anchor="true" data-turn="assistant"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn" tabindex="-1"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal [.text-message+&]:mt-1" dir="auto" data-message-author-role="assistant" data-message-id="8b6cf731-bf12-41f3-bf15-a381cfda1372" data-message-model-slug="gpt-5-2"> Plant extract reduced Ag+ yielding quasi-spherical, crystalline materials sized 51–69 nm. Dose-dependent antibacterial action strongest against Pseudomonas aeruginosa among tested pathogens. High radical scavenging and selective cytotoxicity toward A549 cells with limited normal fibroblast toxicity.